Tourist Satisfaction as a Bridge Between Memorable Tourism Experience and Revisit Intention: An Empirical Study of Aek (Program Studi Ekonomi Syariah, Fakultas Agama Islam Universitas Islam Riau, 2025)
Fluctuations in tourist visits to Aek Sijorni, the lack of variety in tourism activities, inadequate facilities, limited destination information, and suboptimal social interactions have led tourists to feel that their experiences were neither unique nor satisfying. Therefore, this study aims to analyze the influence of memorable tourism experience on the intention to revisit the Aek Sijorni tourist destination, as well as the role of tourist satisfaction as a mediating variable. This research employs a quantitative approach with a random sampling technique, involving 383 respondents who have visited Aek Sijorni. The analysis method uses Structural Equation Modeling - Partial Least Squares (SEM-PLS) with the aid of WarpPLS 7.0 software. The results show that memorable tourism experience significantly affects both satisfaction and revisit intention. Satisfaction was found to mediate the relationship between memorable tourism experience and revisit intention, emphasizing the importance of experience and satisfaction in building tourist loyalty. The implication is that tourist destinations need to create unique experiences through cleanliness, adequate facilities, and culturally based programs. Proper facility management, friendly service, and positive interaction with the local community can enhance tourist satisfaction and loyalty. Therefore, the government and destination managers need to improve service quality, involve local communities in tourism activities, and develop marketing strategies based on cultural values. Infrastructure support and staff training must also be optimized to ensure tourist comfort and enhance the destination’s competitiveness. The limitations of this study lie in its geographically restricted scope, focusing only on a single tourist destination, Aek Sijorni, which means the findings may not be generalizable to other destinations with different characteristics. Additionally, the data collected are self-reported, which may contain subjective perception biases from the respondents. This study also does not explore external factors such as digital promotion or competition dynamics among destinations that may also influence revisit intention.